(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2025)
This study aims to analyze the political role of R.A.A Wirantakusumah V in 1948-1950 which includes his work when he was Republican, became Mayor of Pasundan. The method in this research is the historical method which consists of several stages, namely: heuristics, source criticism (external and internal), interpretation and historiography. Through this research, it can be known, Revolution, there were two opposing groups. Second, role of R. A. A. Wiranatakusumah V work as the Mayor of Pasundan is very central as a liaison between the Republic of Indonesia and the Pasundan State. Although in the Pasundan State there are many factions and groups, R.A.A. Wiranatakusumah V is a Republican who holds fast to the independence and struggle of the Republic of Indonesia. And the end of R. A. A. Wiranatakusumah V political activities was marked by the end of his position as Mayor of Pasundan which was marked by the end of the Pasundan State in 1950 rejoining the of Indonesia.